A cascade-looped thermoacoustic driven cryocooler with different-diameter resonance tubes. Part Ⅱ: Experimental study and comparison. (15th September 2020) - Xu, Jingyuan; Hu, Jianying; Sun, Yanlei; Wang, Huizhi; Wu, Zhanghua; Hu, Jiangfeng; Hochgreb, Simone; Luo, Ercang
Abstract: A small-scale, heat-driven cooling system is required for on-site liquefaction of unconventional natural gas in a distributed station. To meet such demands, we propose a highly efficient heat-driven thermoacoustic cryocooler. This paper presents the experimental results of the proposed system, which is optimized based on previous theoretical analysis. Firstly, we compare two high-temperature heat exchangers with similar heat transfer effectiveness but different flow uniformity. The experimental results show that the heat exchanger with uniform flow can improve system efficiency by 28%. Experimental investigations are then carried out to understand the effect of operating temperatures on system performance. The performance of the system operating at variable heating temperatures is studied. Finally, the reasons for the discrepancy between experiments and calculations are discussed. The experimental results show that the proposed thermoacoustically-driven cryocooler can achieve an exergy efficiency of 10% and a cooling power of 378 W at a heating temperature of 730 K and a cooling temperature of 130 K. This represents a 25% improvement in efficiency compared to the previous record-holder thermoacoustic system. Highlights: A high-efficiency thermoacoustically-driven cryocooler has been developed and tested. The performance of two high-temperature heat exchangers with different flow uniformity are compared. Exergy efficiency of 10% and cooling power of 378 W is achieved at 130 K. Efficiency increases by 25% with respect to the previous record holder system.